The Broader Autism Phenotype, Social Interaction Anxiety, and Loneliness: Implications for Social Functioning - Lamport, Dustin; Zlomke, Kimberly R. (Current psychology (New Brunswick, N.J.), 2014)
Recent research has begun to focus on the subclinical presentation of autistic-like traits in individuals, a construct termed the broader autism phenotype (BAP). The presence of the BAP has been established in both first-degree relatives of individuals with autism as well as in the general population. The current study aimed to examine how self-reported BAP characteristics, social interaction anxiety, and fear of negative evaluation relate to social functioning (specifically, loneliness) in a sample of college students. Results showed that for all subjects, BAP, social interaction anxiety, and fear of negative evaluation did not predict loneliness in a regression model. However, for males these predictors accounted for approximately 48 % of the variance in loneliness scores. Among males, individuals rating themselves as having lower social skills, lower imagination, and higher social interaction anxiety were more likely to also report feeling lonely. These results indicate that the predictors used may function differently among males and females. Although BAP characteristics and social interaction anxiety may not be important correlates of social functioning for females in this sample, they appear to be very important for males’ subjective feelings of loneliness.